OVERCOMING THE CHALLENGE: EFFECTIVE STRATEGIES FOR IMPLEMENTING AUTHENTIC ASSESSMENT - Salsabila, Alifia Zulfi; Amalia, Irma Dwi; Bashith, Abdul (Universitas Tribhuwana Tunggadewi, 2025)
This research aims to find out strategies that can be applied in authentic assessment as a measure of success and as a learning evaluation material to further develop according to the times. The method used in this research is to use a qualitative method with a literature study approach or library research. In digging up information through literature studies, researchers pay attention to the credibility of journals that are tailored to the title in this study. Meanwhile, the analysis technique used is content analysis technique. The results of this study indicate that one of the learning evaluation models relevant to education is the authentic assessment model. Authentic assessment aims to measure the ability of students as a whole, both cognitive (knowledge), affective (attitude), and psychomotor (skills) aspects. The context of applying authentic assessment involves the real world in the form of project tasks. This is done to prepare learners to face real-world situations. In its application, there are certainly factors that influence it. Some of the inhibiting factors in the application of authentic assessment include lack of time, the number of students exceeding the limit, and the lack of teacher understanding of authentic assessment.